Do Internal Auditor and Audit Committee Have Impact on Audit Report Lag for Mining Industry? - Helisa Noviarty; Ayu Puspitasari; Elok Heniwati (Institute of Research and Community Outreach - Petra Christian University, 2021)
The purpose of this study is to examine the effect of the Internal Auditor and Audit Committee on Audit Report Lag (ARL) and the moderating effect of Company Size on the relationship between the Internal Auditor and the Audit Committee on ARL. Using mining sector companies listed on the Indonesia Stock Exchange (BEI) from 2016 to 2018, this study results in the number of observations of 99 cases. The results show that the Internal Auditor and Audit Committee have a negative effect on ARL. The result also shows that Company Size has a moderating effect on the influence of the Internal Auditor and Audit Committee on ARL.